COMPOSITION OF THE ESSENTIAL OILS OF CENTAUREA DIFFUSA LAM. AND CENTAUREA ZEYBEKII WAGENITZ - Altintas, A.; Tugay, O.; Demirci, B.; Baser, K. Husnu C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In Turkey, the genus Centaurea L. (Asteraceae) is represented by 189 species including 120 endemics, distributed particularly in the Southwest, Central and Eastern parts (1-2). The ratio of endemism is quite high (63.4%). Several members of this genus, such as C. cyanus L., C. behen L., C. calcitrapa L., are used in Anatolian folk medicine (3). Aerial parts of Centaurea diffusa Lam. and Centaurea zeybekii Wagenitz were subjected to hydrodistillation for 3 h using a Clevenger-type apparatus and the oils trapped in hexane were analysed by gas chromatography-mass spectrometry (GC-MS). Identification of the essential oil components was carried out by comparison of their relative retention times with those of authentic samples or by comparison of their relative retention index (RRI) to the series of n-alkanes. Computer matching against commercial (Wiley GC/MS Library, Adams Library, MassFinder 2.1 Library) (4-5), and in-house “Baser Library of Essential Oil Constituents” built up by genuine compounds and components of known oils, as well as MS literature data (6-8), were used for the identification. Fifty nine and ninety compounds representing 87.1% and 81.6% of the essential oils were characterized from C. diffusa and C. zeybekii, respectively. eudesmol (45.4%), hexadecanoic acid (4.5%) and hexahydrofarnesyl acetone (4.1%) were the main constituents in the oil of C. diffusa and hexanoic acid (9.3%), hexadecanoic acid (8.6%) and nonacosane (6.4%) were the main constituents in the oil of C. zeybekii.